Cost of Care for HIV-Infected Patients with Co-Occurring Substance Use Disorder or Psychiatric Disease: Report from a Large, Integrated Health Plan - Gerald N. DeLorenze; Ai-Lin Tsai; Michael A. Horberg; Charles P. Quesenberry (AIDS Research and Treatment)
Background. The costs of providing care to HIV-infected (HIV+) patients with co-occurring diagnoses of substance use (SU) disorder or psychiatric disease (PD) are not well documented. It is our objective to evaluate costs in these HIV+ patients receiving care in a large health plan. Methods. We conducted a retrospective cohort study from 1995 to 2010 to compare costs of healthcare in HIV+ patients with and without co-occurring SU disorder and/or PD diagnoses. Estimates of proportional differences in costs (rate ratios) were obtained from repeated measures generalized linear regression. Models were stratified by cost category (e.g., inpatient, outpatient). Results. Mean total healthcare costs per patient per year were higher in HIV+ patients diagnosed with SU disorder or PD compared to HIV+ patients without these comorbid conditions. After controlling for confounders, total mean costs remained significantly higher in patients diagnosed with SU disorder (RR = 1.24, 95% CI = 1.18–1.31) or PD (RR = 1.19, 95% CI = 1.15–1.24). Mean outpatient care costs were significantly greater in patients with both SU disorder and PD (RR = 1.52, 95% CI = 1.41–1.64). Conclusions. Given these higher expenditures in the care of HIV+ patients with comorbid SU disorder and/or PD, greater efforts to facilitate SU disorder or PD treatment initiation and persistence could provide substantial savings.